Analisis Implementasi E-Court pada Pengadilan Negeri Singaraja - Dwi Ruth Bina; Ratna Artha Windari; I Dewa Gede Herman Yudiawan; Made Sugi Hartono; Guntur Frans Gerri (International Forum of Researchers and Lecturers, 2026)
This study aims to analyze the implementation of the e-Court system at the Singaraja District Court in accordance with Supreme Court Regulation (PERMA) Number 7 of 2022, identify the supporting and inhibiting factors influencing its implementation, and evaluate its effectiveness in realizing the principles of simple, fast, and low-cost justice. This research employs a normative legal research method using both statute and conceptual approaches. Legal materials were collected through library research, including legislation, legal doctrines, scholarly publications, and relevant court regulations, and were analyzed using a qualitative descriptive method. The findings reveal that the implementation of the e-Court system at the Singaraja District Court is generally consistent with the provisions of PERMA Number 7 of 2022, encompassing e-Filing, e-Payment, e-Summons, and e-Litigation services. The system has contributed to improving judicial efficiency, transparency, and accessibility by simplifying case administration and reducing procedural delays. Nevertheless, several obstacles continue to affect its optimal implementation, particularly limited information technology infrastructure, unstable internet connectivity, and low levels of digital literacy among non-advocate users. Based on George Edward III’s policy implementation theory, the communication and resource dimensions emerge as the most influential factors determining implementation success, highlighting the importance of effective socialization, adequate infrastructure, and continuous capacity building to enhance the sustainability and effectiveness of electronic court services.